Measuring Entrepreneurial Ecosystems - Erik Stam (Utrecht University, Utrecht University School of Economics, Tjalling C. Koopmans Research Institute, 2017)
How can entrepreneurial ecosystems and productive entrepreneurship can be traced empirically and how is entrepreneurship related to entrepreneurial ecosystems. The analyses in this chapter show the value of taking a systems view on the context of entrepreneurship. We measure entrepreneurial ecosystem elements and use these to compose an entrepreneurial ecosystem index. Next, we measure the output of entrepreneurial ecosystems with different indicators of high-growth firms. We use the 12 provinces of the Netherlands as a test case for measuring the entrepreneurial ecosystem elements, composing an entrepreneurial ecosystem index and relate this to entrepreneurial outputs. The prevalence of high-growth firms relates to the overall value of the entrepreneurial ecosystem index, but not to individual elements of the entrepreneurial ecosystem. The model fit increases once we introduce a multiplicative index and a non-linear model. By measuring entrepreneurial ecosystems and their outputs in this way we move from the ecosystem metaphor to a complex system model of the entrepreneurial economy.
Keywords: 330; Entrepreneurial ecosystem; complex systems; entrepreneurial ecosystem index; entrepreneurship; regional development